The Impact of a Ketogenic Diet and Liver Dysfunction on Serum Very Long‐Chain Fatty Acids Levels. Issue 4 (31st January 2013) - Stradomska, T. J.; Bachański, M.; Pawłowska, J.; Syczewska, M.; Stolarczyk, A.; Tylki‐Szymańska, A.
Abstract: Peroxisomes play an essential role in mammalian cellular metabolism, particularly in oxidation fatty acid pathways. Serum very long‐chain fatty acids (VLCFA), the main biochemical diagnostic parameters for peroxisomal disorders, were examined in 25 neurological patients with epilepsy on a ketogenic diet and 27 patients with liver dysfunction. The data show that patients on a ketogenic diet have increased levels of C22:0 and C24:0, but not C26:0, and normal C24:0/C22:0 and C26:0/C22:0. Patients with liver insufficiency showed a slightly elevated level of C26:0, a normal level of C24:0 and a decreased level of C22:0; thus in 21/27 the ratio of C24:0/C22:0 was increased and 15/27 the ratio of C26:0/C22:0 was increased.